Systematic study of one-loop realizations of d = 7 long-range 0νββ decay operators - Ping-Tao Chen; Gui-Jun Ding; Chang-Yuan Yao (Journal of High Energy Physics, 2023)
Abstract We study the systematical one-loop decomposition of the dimension-7 long-range 0νββ decay operators. We find that there are 3 genuine one-loop topologies and 8 diagrams. The procedure to determine the SM quantum number assignments for both internal and external fields is presented. The Majorana neutrino mass in long-range 0νββ models is discussed. We also present a one-loop 0νββ decay model which produces Majorana neutrino mass at three-loop level. The phenomenological predictions for light neutrino mass and 0νββ decay half-life time including both mass mechanism and long-range contribution are studied.